Using Task-based in Teaching Writing - Boonbongkotrat, Nattakrita; Kosiyakul, Siwaporn; Pitukwong, Kusuma (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
This article aimed to study Task-based Learning’s definitions, types, and components to apply in teaching writing skill using Pedagogical Task and Rehearsal Rational with the activities as 1) Listing 2) Ordering and Sorting 3) Sharing Personal Experiences and 4) Creative task. The instructor set the objective as letting learners are able to write narrative text following the steps: 1) Pre-Task 2) Task Cycle 3) Language Focus and 4) Lesson Summary